The thickness and volume of the choroid, outer retinal layers and retinal pigment epithelium layer changes in patients with diabetic retinopathy - Wang, Xiang-Ning (Int J Ophthalmol, 2018)
AIM: To evaluate the thickness and volume changes of the choroidal, outer retinal layers (ORL) and retinal pigment epithelium (RPE) in patients with diabetic retinopathy (DR) using optical coherence tomography (OCT) and correlate them with visual acuity. METHODS: We carried out a retrospective observational case series. Consecutive DR patients were recruited for color fundus photography and OCT assessment. The RPE, ORL and choroidal thickness were measured. The correlation with the best-corrected visual acuity (BCVA) was also investigated. RESULTS: The study included 128 eyes, comprising 45 eyes of 25 diabetic macular edema (DME) patients, 34 eyes of 20 DR without DME (non-DME) patients, and 49 eyes of 25 age-matched normal individuals. The choroidal thickness in DR patients were decreased statistically significantly compared with the control group (P<0.05). The mean macular ORL thickness in DME (73.02±15.34 µm) and non-DME groups (76.35±7.32 µm) were decreased statistically significantly compared with the control group (80.20±5.85 µm; P=0.006, P=0.013, respectively). In both the non-DME and DME groups, the RPE thickness were decreased compared with the control group (P<0.05), except in the macular and central ring. The BCVA were significant interactions with the total inner retinal volume and macular RPE thickness in the DME group (r=0.115, P<0.001, r=-0.013, P=0.017, respectively). CONCLUSION: The choroid, ORL and RPE thickness are significantly decreased in DR patients compared with controls in different segments.